Endothelial cell dysfunction in viral hemorrhage and edema - Mackow, Erich R.; Gorbunova, Elena E.; Gavrilovskaya, Irina N. (Frontiers in Microbiology, 2015)
The endothelium maintains a vascular barrier by controlling platelet and immune cell interactions, capillary tone and interendothelial cell adherence. Here we suggest common elements in play during viral infection of the endothelium that alter normal endothelial cell functions and contribute to lethal hemorrhagic or edematous diseases. In viral reservoir hosts, infection of capillaries and lymphatic vessels may direct immunotolerance without disease, but in the absence of these cognate interactions they direct the delayed onset of human disease characterized by thrombocytopenia and vascular leakage in a severe endothelial dysfunction syndrome. Here we present insight into endothelial cell controls of hemostasis, immune response and capillary permeability that are altered by viral infection of the endothelium.